Investigation of factors involved in Moroccan economic development - Khellat Mouna; Bouich Amal; Baddih Hindou; Guaita Pradas Inmaculada (E3S Web of Conferences, 2023)
Recently, Morocco has initiated an extensive program of economic, financial, and social reforms aimed at achieving sustainable development. These reforms are mostly structural changes that take years to yield results. The green plan proposed by Morocco integrates an approach that addresses issues related to water scarcity and offers a chance to make the agriculture sector an engine of the economy, thereby rebalancing the trade balance. The strategy aims to give the sector a dynamic of balanced evolution, exploit the potential for progress, preserve the balance of social and economic issues, and support the profound change that the global agri-food system is undergoing. This investigation reveals that demographic development has a tangible impact on economic and sustainable development, and we must manage the risks associated with changes in today’s world.